How to improve the system of care for adolescents with emotional and behavioural problems from the perspective of care providers: a concept mapping approach - Bosakova, Lucia; Dankulincova Veselska, Zuzana; Filakovska Bobakova, Daniela (Health research policy and systems, 2024)
BACKGROUND: Emotional and behavioural problems (EBP) are the most common mental health issues during adolescence, and their incidence has increased in recent years. The system of care for adolescents with EBP is known to have several problems, making the provision of care less than optimal, and attention needs to be given to potential improvements. We, therefore, aimed to examine what needs to be done to improve the system of care for adolescents with EBP and to assess the urgency and feasibility of the proposed measures from the perspective of care providers. METHODS: We used Concept mapping, a participatory mixed-method research, based on qualitative data collection and quantitative data analysis. A total of 33 stakeholders from 17 institutions participated in our study, including psychologists, pedagogues for children with special needs, teachers, educational counsellors, social workers and child psychiatrists. RESULTS: Respondents identified 43 ideas for improving of the system of care for adolescents with EBP grouped into 5 clusters related to increasing the competencies of care providers, changes at schools and school systems, support for existing services, transparency of the care system in institutions and public administration, and the adjustment of legislative conditions. The most urgent and feasible proposals were related to the support of awareness-raising activities on the topic of EBP, the creation of effective screening tools for the identification of EBP in adolescents, strengthening the role of parents in the process of care, comprehensive work with the family, creation of multidisciplinary support teams and intersectoral cooperation. CONCLUSIONS: Measures which are more accessible and responsive to the pitfalls of the care system, together with those strengthening the role of families and schools, have greater potential for improvements which are in favour of adolescents with EBP. Care providers should be invited more often and much more involved in the discussion and the co-creation of measures to improve the system of care for adolescents with EBP.
Keywords: mladiství; Child; Emotional and behavioural problems; Emotions; dítě; rodiče; Care providers; Children; emoce; Concept mapping; lidé; Parents; Adolescent; Humans; Adolescents; System of care; problémové chování; Problem Behavior